If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -6 = 4a + -1a Combine like terms: 4a + -1a = 3a -6 = 3a Solving -6 = 3a Solving for variable 'a'. Move all terms containing a to the left, all other terms to the right. Add '-3a' to each side of the equation. -6 + -3a = 3a + -3a Combine like terms: 3a + -3a = 0 -6 + -3a = 0 Add '6' to each side of the equation. -6 + 6 + -3a = 0 + 6 Combine like terms: -6 + 6 = 0 0 + -3a = 0 + 6 -3a = 0 + 6 Combine like terms: 0 + 6 = 6 -3a = 6 Divide each side by '-3'. a = -2 Simplifying a = -2
| 7x+54=3x+187 | | 4+4h(7)-2h= | | 3x-15=4x+2 | | -3=4b+1-3b | | 4x+b=2x+c | | 32k-32=-5k-32 | | -6=5x-4x | | 8+3(4v-2)= | | -2=3v-6-2 | | 8x^2-10x-63=0 | | 10+30b=-20 | | 3(7h-1)= | | -6-30v=54 | | -y-8+6y=-9+5y+1 | | 4r+6-2r= | | q(9+2)-7= | | -10(x+4)+48=-16-16 | | 15x-9-4x+2=4 | | 9(t-6)-4(3+t)= | | 24x-8x= | | 1=7z-(-1) | | 30=-30n-30 | | -9.9+a=-25 | | x^2+8x=24 | | 5n+5n=10 | | -(x+8)=3(6x-1) | | Y-(-6.1)=20.5 | | 8(j-3)=4j+9j-14 | | -8=6a-2a | | 2m-21=9m+7 | | 5(y-3)=8(y+6) | | 6(x+4)=2(x+8) |